Effects of Multiple Doses of Dichloroacetate on GSTZ1 Expression and Activity in Liver and Extrahepatic Tissues of Young and Adult Rats - Squirewell, Edwin J. (Drug Metab Dispos, 2020)
Glutathione transferase zeta 1 (GSTZ1), expressed in liver and several extrahepatic tissues, catalyzes dechlorination of dichloroacetate (DCA) to glyoxylate. DCA inactivates GSTZ1, leading to autoinhibition of its metabolism. DCA is an investigational drug for treating several congenital and acquired disorders of mitochondrial energy metabolism, including cancer. The main adverse effect of DCA, reversible peripheral neuropathy, is more common in adults treated long-term than in children, who metabolize DCA more quickly after multiple doses. One dose of DCA to Sprague Dawley rats reduced GSTZ1 expression and activity more in liver than in extrahepatic tissues; however, the effects of multiple doses of DCA that mimic its therapeutic use have not been studied. Here, we examined the expression and activity of GSTZ1 in cytosol and mitochondria of liver, kidney, heart, and brain 24 hours after completion of 8-day oral dosing of 100 mg/kg per day sodium DCA to juvenile and adult Sprague Dawley rats. Activity was measured with DCA and with 1,2-epoxy-3-(4-nitrophenoxy)propane (EPNPP), reported to be a GSTZ1-selective substrate. In DCA-treated rats, liver retained higher expression and activity of GSTZ1 with DCA than other tissues, irrespective of rodent age. DCA-treated juvenile rats retained more GSTZ1 activity with DCA than adults. Consistent with this finding, there was less measurable DCA in tissues of juvenile than adult rats. DCA-treated rats retained activity with EPNPP, despite losing over 98% of GSTZ1 protein. These data provide insight into the differences between children and adults in DCA elimination under a therapeutic regimen and confirm that the liver contributes more to DCA metabolism than other tissues. SIGNIFICANCE STATEMENT: Dichloroacetate (DCA) is one of few drugs exhibiting higher clearance from children than adults, after repeated doses, for reasons that are unclear. We hypothesized that juveniles retain more glutathione transferase zeta 1 (GSTZ1) than adults in tissues after multiple DCA doses and found this was the case for liver and kidney, with rat as a model to assess GSTZ1 protein expression and activity with DCA. Although 1,2-epoxy-3-(4-nitrophenoxy)propane was reported to be a selective GSTZ1 substrate, its activity was not reduced in concert with GSTZ1 protein.